Experimental study of heat transfer of buried finned pipe for ground source heat pump applications - Koyun, Ahmet; Demir, Hakan; Torun, Zakir (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Ground heat exchangers have vital importance for ground source heat pump applications. Various configurations tried to improve heat transfer in the soil. A new kind of aluminium finned pipe buried in the soil for this aim. In order to compare effectiveness of the Al finned pipe over the traditional PPRC pipe an experimental study carried out. The experimental GSHP system was installed at Yildiz Technical University Davupasa Campus on 800 m(2) surface area with no special surface cover. Temperature data were collected using thermocouples buried in soil horizontally and vertically at various distances from the pipe center and at the inlet and the outlet of the ground heat exchanger. Experimental results were compared with results from analytical study. To compare effectiveness of the Al finned pipe and PPRC pipe a new parameter defined as transferred amount of heat per unit mass of working fluid per unit time for this aim. it is found that Al finned pipe has higher heat transfer values than the traditional PPRC pipe. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Finned pipe; Heat transfer; Ground source heat pump; Buried pipe; EXCHANGER; MODEL; Thermodynamics; Mechanics